Towards an Explicit Instructor Model - Huapaya, Constanza R. (2003)
Our long term aim is to reach an easily available, flexible and complete instructor model of an Intelligent Tutoring System. In order to get our objective, we propose a new instructor model where intentions of actual instructors are shaped into adaptive tutoring strategies. The key idea involves an instructor acting as she if was a knowledge engineer, proposing goals and softgoals, and choosing resources and tasks in order to reach them through an ITS. We present a preliminary conceptual approach to an explicit instructor model. When an author/instructor delivers to system her personal experience, ITS captures these individual features. Each instance of the model would be an instructor with a clear profile acting according to specific behavior. So, a student would choose a personal instructor that matches better her learning style.